Predation by Sparrowhawks Accipiter nisus and vulnerability of prey - Solonen, T. (BirdLife Finland, 2000)
Prey selection of the Sparrowhawk (Accipiter nisus) was studied in northern Finland during 1982-1993. A total of 540 prey items (all birds) were recorded from the surroundings of 12 nests. For each prey species a vulnerability index was calculated as the ratio between its proportion in the Sparrowhawk's diet and its proportion in the land bird community (data from the whole of the Oulanka National Park, and spruce forests only). The average prey individual weighed 52 g, whereas the average breeding bird weighed 36 g in the spruce forests and 24 gin the whole of the Oulanka National Park area . Prey vulnerability increased with increasing prey body mass. The result could be interpreted in the light of the optimal foraging theory, large prey being the most profitable among the Sparrowhawks' prey-size range. In the whole of Oulanka data, open habitat species were caught relatively more frequently than forest species, and prey vulnerability correlated negatively with prey abundance . Foraging behaviour and the nest site of the prey species were not related to their vulnerability . Phylogenetic analyses revealed a significant correlation between prey vulnerability and plumage brightness, after the effects of body mass and abundance of prey species were controlled for. Higher relative predation risk of bright species give support to the `sexual selection' hypothesis but not to the `unprofitable prey' hypothesis explaining prey vulnerability .